PENGARUH PENAMBAHAN ADITIF 5 PPM ION Cu2+ TERHADAP PERTUMBUHAN KERAK Mg PADA PIPA LAMINER DENGAN LAJU 30 ML/MENIT - Vicky Aditya (Universitas Muhammadiyah Semarang, 2019)
Current industries, both large and small are still using boiler as generator power. In boilers having complex problems in their operations, what usually happens is that the air supply quality kettles that are less qualified is taken from well, river, sea air that have salts that will become crust in the heat transfer process and the process that goes on in the industry. The purpose of this research was to develop a crust- forming simulator, to understand the mechanism of MgCO3 crust control with the addition of Cu2+ 5 ppm ions in the pipe and to assess crustal morphology. The results obtained during the test by reacting MgCl2 and Na2CO3 using a 300 ppm Mg2+ concentrate solution with the exchange of induction time. The results of this study obtained the induction time without the addition of 24 minutes with a conductivity value of 8522 µS whereas with the addition of Cu2+ 5 ppm the conductivity value was 8636 µS for 30 minutes. The SEM results show that the morphological form of MgCO3 crust which was originally a tomb is an irregular and smaller size.